Wisconsin and the shaping of American law - Ranney, Joseph A., 1952- (The University of Wisconsin Press, 2017)
"State laws affect nearly every aspect of our daily lives--our safety, personal relationships, and business dealings--but receive less scholarly attention than federal laws and courts. [The author] looks at how state laws have evolved and shaped American history, through the lens of the historically influential state of Wisconsin. Organized around periods of social need and turmoil, the book considers the role of states as legal laboratories in establishing American authority west of the Appalachians, in both implementing and limiting Jacksonian reforms and in navigating legal crises before and during the Civil War--including Wisconsin's invocation of sovereignty to defy federal fugitive slave laws. [The author] also surveys judicial revolts, the reforms of the Progressive era, and legislative responses to struggles for civil rights by immigrants, women, Native Americans, and minorities in the nineteenth and twentieth centuries. Since the 1960s, battles have been fought at the state level over such issues as school vouchers, voting, and abortion rights."--